Determinantes estruturais da saúde: relação com o acesso e qualidade dos serviços de saúde e carga global de edentulismo em 204 países - Fagundes, Maria Laura Braccini (2023)
Although health problems are experienced individually, they are public and political in nature; and, despite the macro determinants of health being a central factor in explaining the health conditions of the populations, their relationship with access to health services and oral health remains not fully comprehended. Considering the exposed context, this thesis aimed to analyze the relationship between the macro determinants of health and the access and quality of health services and the global burden of edentulism in 204 countries and territories in 2010 and 2019. For this purpose, 2 articles were developed. The first one assessed the possible relationship between the macro determinants of health and the Healthcare Access and Quality Index (HAQ) in 2010 and 2019 globally. The correlation between the HAQ index and the exposure variables were performed using Spearman correlation test. The second study sought to provide a comprehensive description of the estimates of edentulism by the macro determinants of health in the same period and countries, and the estimates were reported as rates (cases/100,000 people), for people of both sexes aged 55 and over. Both studies were ecological and used data from the Global Burden of Disease Study (GBD) cycle 2019. The exposures for both studies were the macro determinants considering their 5 dimensions - governance, macroeconomic policy, social policy, public policies and cultural values, using variables made available by the World Bank and which, according to the literature, can be considered proxies for these macro determinants: governance, per capita gross domestic product (GDP), sociodemographic index (SDI), public health spending and percentage of women in parliament. The findings of the first study suggest important inequalities between countries in the performance of health systems. Governance, GDP and SDI showed strong correlations with HAQ. The findings of the second study point to persistent inequalities in the distribution of edentulism between countries around the world. The most privileged countries, with greater economic development, better governance, better social and public policies, presented higher rates of edentulism, which is probably related to the hegemonic model of oral health care. These studies expand the approaches adopted so far and demonstrate the relevance of exploring other dimensions of the macro determinants and their potential contribution to access and quality of healthcare as well as to the distribution of edentulism worldwide. By focusing on these contextual determinants, these analyzes reinforce the evidence base to bring quality and access to health care closer to everyone's reality, and demonstrate the importance of rethinking the oral health care model and moving towards patient-centered care.